Analisis Kinerja Situs Web Perusahaan Asuransi Umum Terbuka Studi Kasus: 8 (Delapan) Perusahaan Asuransi Umum Terbuka di Indonesia - Djojo, Brata Wibawa (Binus Business Review, 2012)
The companyâs product and service can be uploaded and accessed in website. It will make the customer easier to find for any information of product offered or about the company itself through companyâs website. Product(s) and service(s) information of the general insurance company in the website are the important things to make their customer learn about the product, know the company and (perhaps) make a transaction on there. This research is to measure the website performance of the go-public general insurance companies: how they fulfill the customer expectation of the information and service provided in their website properly. The research uses a non-statistical method, Quality Function Deployment (QFD) methodology. It uses House of Quality tool in graph and matrices to gather the Voice of Customer (VoC) for customerâs requirements of website performance and the Voice of the Engineer (Technical Requirements), which is described for the website characteristic in terms of the function itself. Through this analysis, it will be set the development targets of the website performance of 8 (eight) go-public general insurance companies in Indonesia. It may be as an input for each company to review their website performance further.